1999
DOI: 10.1071/wf00014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat on seed germination of nine woody Cistaceae species

Abstract: The influence of high temperatures on germination of four Cistus and five Halimium taxa is analysed. Seeds were heated to a range of temperatures (from 50ºC to 150ºC) and a range of exposure times (from 1 to 60 min), simulating those heat conditions registered on the soil surface during wildfires. After the thermal pretreatments, seeds were sown in plastic Petri dishes and monitored for germination over 60 days. For all the species, germination was increased significantly over the control set (untreated seeds)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
62
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 20 publications
6
62
1
1
Order By: Relevance
“…Keeley 1991;Tarrega et al 1992;Herranz et al 1998). However, our study showed that after the exposure to high temperatures, seeds still germinated.…”
contrasting
confidence: 38%
“…Keeley 1991;Tarrega et al 1992;Herranz et al 1998). However, our study showed that after the exposure to high temperatures, seeds still germinated.…”
contrasting
confidence: 38%
“…and Pinus spp., is stimulated by increased heat [31]. However, their germination does not depend exclusively on the thermal increase caused by fire [21,42], as they also germinate under control conditions. The viability of seeds and the survival of seedlings in natural conditions are key factors for sexual regeneration of woody species [3].…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination is influenced by internal factors causing dormancy including seed coat factors, embryo factors or inhibitors (Agrawal, Dadlani 1995). There are different methods to overcome dormancy, which vary from species to species, such as heating (Herranz et al 1998), stratification, scarification (Narbona et al 2003) and gibberellin application. Stratification and GA 3 treatments of seeds were effective to .…”
mentioning
confidence: 99%